Anti-Tuberculosis Drugs against the Resistance Level of Mycobacterium tuberculosis isolates - Sutanto, Yusup Subagio; Sutanto, Magdalena Sutanto; Harti, Agnes Sri (KEMAS: Jurnal Kesehatan Masyarakat, 2021)
Prolonged MDR-TB therapy can have side effects, namely a correlation between cure rates and changes in bacterial profiles related to resistance to anti-tuberculosis drugs (ATD) which can affect the incidence rate of MTB and MDR-TB in a region. The research objective was to analyze the effectiveness of the type of ATD against the resistance level of Mycobacterium tuberculosis (MTB) isolates with the incidence of tuberculosis (TB) and MDR-TB. The research method used was a retrospective cohort based on tracing medical record data at the Surakarta City Center General Hospital 2016 until 2017 with total sampling. The independent variable of this study was the type of ATD, while the dependent variable was the resistance level of MTB isolates. The characteristics of the most patient respondent suspect TB were male with the level of resistance of MTB isolates to ATD relatively varied. The results of the analysis of different tests showed a p value of 0.000 so that the p value was <0.05, so there was an effect of the type of ATD (Strepttomycin, Isoniazid, Rifampicin and Ethambutol) on the resistance of TB isolates from patients with suspected TB. This is useful to determine the success of TB therapy in terms of mortality and the effectiveness of therapy in TB patients.